1996
DOI: 10.1016/s0001-8686(96)00307-7
|View full text |Cite
|
Sign up to set email alerts
|

A general model to describe the electrostatic potential at electrolyte oxide interfaces

Abstract: Colloid chemists have proposed several theories to describe the charging mechanism of metal oxides in electrolyte solutions and the resulting electrical double layer at the oxide surface. In this paper a new general theory to describe the electrostatic potential at the metal oxide electrolyte solution interface is presented. This theory describes the variations of the electrostatic potential as a function of the differential double layer capacitance and the intrinsic buffer capacity. ISFET measurements are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
299
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(325 citation statements)
references
References 12 publications
(3 reference statements)
21
299
0
5
Order By: Relevance
“…The behavior of the device on bare quartz is reproduced by the parameters N S = 1.02 ± 0.11 10 16 cm -2 , Q int = 2.69 ± 0.24 µC and α = -15.5 ± 1.7 mV. The value of Ns is in agreement with other models; 26,27 if the channel area is A ch = 3.02 10 33 cm 2 and the thickness of pentacene is 15 nm, Q int corresponds to a maximum density of dopants (each deproto3 nated site yields a charge in pentacene) of approximately 4 10 20 cm -3 , i.e. 4 charges per 14 unit cells.…”
Section: Acs Applied Materials and Interfacessupporting
confidence: 84%
See 1 more Smart Citation
“…The behavior of the device on bare quartz is reproduced by the parameters N S = 1.02 ± 0.11 10 16 cm -2 , Q int = 2.69 ± 0.24 µC and α = -15.5 ± 1.7 mV. The value of Ns is in agreement with other models; 26,27 if the channel area is A ch = 3.02 10 33 cm 2 and the thickness of pentacene is 15 nm, Q int corresponds to a maximum density of dopants (each deproto3 nated site yields a charge in pentacene) of approximately 4 10 20 cm -3 , i.e. 4 charges per 14 unit cells.…”
Section: Acs Applied Materials and Interfacessupporting
confidence: 84%
“…In eq 9, following van Hal et al, 26 a linear dependence of Ψ B on pH (in our observed range) is assumed through the coeffi3 cient α. The total charge Q P5 , as well as the charge contributed by the quartz surface Q q and the capacitive charge Q 1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the site binding model of EDL, 45 Further increase in pH value leads to decrease in noise PSD. The maximum noise PSD level appears pH~5, which is close to the point of zero charge of SiN x .…”
Section: Origin Of the Nanopore Flicker Noisementioning
confidence: 99%
“…are those of a capacitance, describing the sensitivity of the surface charge to a change in the local potential, which is sometimes denoted as regulation capacitance [10] or a surface buffer capacitance [26]. In the following, we will denote the nondimensional form of this capacitance as…”
Section: Modelmentioning
confidence: 99%